Characterization of non -Shiga toxin- producing Escherichia coli O157 strains isolated from dogs - Bentancor, Adriana (2010)
Fil: Bentancor, Adriana. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias. Microbiología; Argentina.